A Needs-Based Tahfidz Curriculum Model for Enhancing Al-Qur’an Memorization - Aghist Zumrotusa'adah; Nilna Fadlillah (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This study aims to analyze the policy basis, objectives, and implementation of the curriculum for the Qur’an memorization enhancement program at the Mambaul Hikmah Islamic Boarding School in Sumber Karang, Dlanggu, Mojokerto. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model and validated through triangulation. The results indicate that the curriculum was designed in response to the low quality of students’ memorization and was therefore developed systematically and based on their needs. The curriculum’s objectives are to improve the quality of memorization while fostering discipline and a sense of responsibility. Its implementation utilizes the wahdah, talaqqi, tasmi’, and muroja’ah methods through a structured learning and evaluation system. These findings indicate that the tahfidz reinforcement curriculum is capable of comprehensively improving the quality of students’ memorization and of producing a needs-based tahfidz curriculum model that can be implemented in Islamic educational institutions with similar characteristics.